Sexual Function of Patients with Deep Endometriosis after Surgical Treatment: A Systematic Review - Graziele Vidoto Cervantes; Paulo Augusto Ayroza Galvão Ribeiro; Mariana Carpenedo Tomasi; Daniela Farah; Helizabet Salomão Abdalla Ayroza Ribeiro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective To review the current state of knowledge on the impact of the surgical treatment on the sexual function and dyspareunia of deep endometriosis patients. Data Source A systematic review was conducted in accordance with the Meta-Analysis of Observational Studies in Epidemiology (MOOSE) guidelines. We conducted systematic searches in the PubMed, EMBASE, LILACS, and Web of Science databases from inception until December 2022. The eligibility criteria were studies including: preoperative and postoperative comparative analyses; patients with a diagnosis of deep endometriosis; and questionnaires to measure sexual quality of life. Study Selection Two reviewers screened and reviewed 1,100 full-text articles to analyze sexual function after the surgical treatment for deep endometriosis. The risk of bias was assessed using the Newcastle-Ottawa scale for observational studies and the Cochrane Collaboration's tool for randomized controlled trials. The present study was registered at the International Prospective Register of Systematic Reviews (PROSPERO; registration CRD42021289742). Data Collection General variables about the studies, the surgical technique, complementary treatments, and questionnaires were inserted in an Microsoft Excel 2010 (Microsoft Corp., Redmond, WA, United States) spreadsheet. Synthesis of Data We included 20 studies in which the videolaparoscopy technique was used for the excision of deep infiltrating endometriosis. A meta-analysis could not be performed due to the substantial heterogeneity among the studies. Classes III and IV of the revised American Fertility Society classification were predominant and multiple surgical techniques for the treatment of endometriosis were performed. Standardized and validated questionnaires were applied to evaluate sexual function. Conclusion Laparoscopic surgery is a complex procedure that involves multiple organs, and it has been proved to be effective in improving sexual function and dyspareunia in women with deep infiltrating endometriosis.